Diagnostic Accuracy of Frozen Section in Salivary Gland Neoplasms (Journal of Rashid Latif Medical College, 2022)
Introduction: Research over the years has systematically revealed thatmorphological, histological, and molecular data from human cancersavailable to pathologists has revolutionized quantitative systems science. Bymeasuring morphological parameters such as tumor stage and grade, it isnow possible to integrate relatively large data sets thus reconceptualizationof knowledge available, provides better prediction of the behavior of tumorsand their interaction with the host. Histological diagnosis prior to surgery isnot possible, as incisional biopsies are contraindicated due to the possibilityof facial nerve injury and incomplete resection of the tumor. Objective: Tocompare the results of the frozen section examination with definitivehistological diagnosis. Identifying malignancy intraoperatively can have asignificant impact on the management of the salivary gland tumors.Materials and Methods: The study was done in Histopathology departmentof SIMS/Services hospital, Lahore. 40 cases of salivary gland neoplasmspreviously diagnosed on FNAC. Results: Comparing the perioperativeresult with definitive diagnosis, 10% (6/40) were true positive, 77.5% (31/40)true negative, 7.5% (3/40) false positive, 0% (0/40) false negative,prevalence, 66.6% positive predictive value and 100% negative predictivevalue. Thus, the sensitivity of frozen section for malignancy was 100% andthe specificity was 91%. Conclusion: We consider that frozen sectionexamination for salivary gland neoplasms is not sufficient on its own fordeciding on the best management. Their interpretation must be correlatedwith clinical and intraoperative findings, in association with surgeon'sexperience.